2022
DOI: 10.1186/s12879-022-07803-7
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Distribution Width as a predictor of community acquired sepsis in patients prospectively enrolled at the Emergency Department

Abstract: Background Monocyte Distribution Width (MDW), a simple cellular marker of innate monocyte activation, can be used for the early recognition of sepsis. We performed an observational prospective monocentric study to assess the predictive role of MDW in detecting sepsis in a sample of consecutive patients presenting at the Emergency Department. Methods Prospective observational study using demographic and clinical characteristics, past medical histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…Those findings are consistent with the previous reports 4 14 . The cut-off value 22 for sepsis prediction, as determined in our study, was similar to that reported by Jo et al 6 , Polili et al 13 , 17 and Hausfater et al 19 , yet slightly higher than values obtained in other studies 4 , 5 , 7 , 10 12 , 14 17 , 19 . This could be explained by the type of anticoagulant used for blood samples.…”
Section: Discussionsupporting
confidence: 90%
“…Those findings are consistent with the previous reports 4 14 . The cut-off value 22 for sepsis prediction, as determined in our study, was similar to that reported by Jo et al 6 , Polili et al 13 , 17 and Hausfater et al 19 , yet slightly higher than values obtained in other studies 4 , 5 , 7 , 10 12 , 14 17 , 19 . This could be explained by the type of anticoagulant used for blood samples.…”
Section: Discussionsupporting
confidence: 90%